Immune status against diphtheria in healthy adults - Jesheera M Kutty; Bijayraj RajanBabu; Sohanlal Thiruvoth (Journal of Family Medicine and Primary Care, 2019)
Outbreaks of diphtheria continue to occur in Kerala with an age shift to older population. Antibody seroprevalence studies are essential to understand the immune status of the community and to develop an effective immunization strategy. Aim: To assess the necessity of diphtheria vaccination among adults. Settings and Design: Cross-sectional study, among 152 healthy adults (>18 years).Methods and Materials: Diphtheria IgG antibody detection was performed by using ELISA technique. Results: Out of 152 study population, 14 (9.2%) individuals had very low antibody levels, requiring basic immunization, 123 (80.9%) needed booster vaccination, 12 (7.9%) would need a booster dose in 5 years and 3 (2%) would need a booster dose in 7 years to maintain adequate antibody levels. Out of the total, 131 (86.2%) individuals had completed childhood immunization and 21 (13.8%) had incomplete or no immunization during childhood. In the population who had completed childhood immunization, 4 (3%) had very low antibody levels requiring basic immunization and 113 (86%) had antibody levels needing booster vaccine soon, with the remaining 14 (10.6%) individuals requiring a booster vaccine after 5 years and 7 years. In the partially immunized/unimmunized population, 10 (47.6%) had antibody levels requiring basic immunization and another 10 (47.6%) had antibody levels low enough to warrant a booster vaccine. Conclusions: Majority of the subjects who had completed childhood immunization showed an inadequate immunity against diphtheria during adulthood. This indicates waning immunity against diphtheria. Hence, modifying the present diphtheria vaccination strategy to include booster doses during adulthood is essential. Context: Even in developed countries where nearly 100% universal immunization is achieved, diphtheria outbreaks are known to occur. Several seroprevalence studies have been conducted in those regions to determine whether those populations have adequate levels of antibodies against diphtheria. In India, sporadic outbreaks occur, and an increasing number of diphtheria cases are being reported over the last few years. Large outbreaks in Kerala 2016 were about 533 cases. Recent outbreaks in 2019, in Trivandrum, about 175 cases were suspected and 19 cases were confirmed in laboratory. However, Indian studies to determine whether the adult population has adequate protective antibody levels are lacking. Knowing the immune status of the population and devising an appropriate strategies to prevent outbreaks of diphtheria are the integral parts of primary care. These concerns are the basis and evaluation of the seroprevalence of IgG antibody levels against diphtheria antitoxin among healthy adults in our region in this study.